The influence of the autonomic nervous system in the control of erythropoietin secretion in the hypoxic rat. - Beynon, G (1977)
1. Erythropoietin has been measured in the serum of hypoxic rats that have been exposed to 6 hr of hypoxia, by use of a biological assay. 2. The effects of section of splanchnic, renal and sinus nerves on the concentration of Erythropoietin present in the serum ofthe hypoxic animals has been investigated. 3. Serum levels of Erythropoietin were reduced in the hypoxic animals immediately after cutting the splanchnic nerves, but unaltered one week after the operation. 4. The concentration of Erythropoietin in the serum of hypoxic rats was increased by the secretion of the renal nerves. Section of the sinus nerves abolished the effect. 5. Elevated levels of Erythropoietin were present in the sera of hypoxic rats immediately after section of the sinus nerves. The effect was still obtained when the animals were exposed to hypoxia 1 week after cutting the nerves, though in attenuated form. 6. The rise in the concentration of the hormone after chronic section of the sinus nerves was estimated as as 261% (fiducial limits 167-513, P = 0-05), by parallel line bio-assay. 7. The concentration of Erythropoietin in the serum of hypoxic rats was progressively elevated as the arterial PO2 of the animals was reduced. Section of the sinus nerves did not alter the secretion of Erythropoietin in these experiments.